Effectiveness of the 2020 Village Fund Direct Cash Assistance Program in West Kawangkoan District Minahasa Regency - Menly Enjoi Sondakh, Boby; P. Lengkong, Johny; J. Waleleng, Grace (Journal of Public Administration and Government, 2025)
Direct Cash Assistance is a program issued by the government in the form of direct cash assistance or cash assistance. Direct Cash Assistance was created to ease the burden on people affected by the Covid 19 Pandemic. This study aims to analyse the effectiveness of the 2020 Village Fund Cash Assistance Program in West Kawangkoan District. This study uses the theory of effectiveness from Edy Sutrisno, which includes the following indicators: Programme Understanding, On Target, Timeliness, Goal Achievement, and Real Change. This research uses qualitative research methods with descriptive explanations, involving 13 informants consisting of 5 village heads, sub-district heads, and 7 community members. The results of this study show that the government has not optimised the data collection process. There are community members who fulfil the criteria as recipients of Direct Cash Assistance who are not recorded as recipients. The data collection process was not on target, as the government was still selective in data collection. In addition, the timing of the distribution of Direct Cash Assistance was ineffective. The distribution was delayed due to delays in the disbursement of the Village Fund. On the positive side, the Direct Cash Transfer had a favorable impact on people's lives during the Covid-19 Pandemic, helping to reduce the cost of living, although the impact was temporary.